Study Of Some Aspects Of Nutrition And Culture Of Malaysian Freshwater Catfish Mystus Nemurus (C. & V.) - Salim Khan, Mohammad (1993)

(untitled)
Mystus nemurus (C.&V.) has enormous potential of becoming a cultured species in Malaysia . In the absence of information on import ant nutritional requirements of the species,aquaculture development could be considerably limited. With the objective of introducing the species to aquaculture , the following studies were conducted : i ) digestibility of M .nemurus with potential feed ingredients , such as fish meal , soybean meal , rice bran , maize , copra meal and chicken viscera ; ii ) optimum dietary protein requirement of the species under tank and pond culture conditions using six isoenergetic practical diets that contained 27 , 32 , 37 , 42 , 47 and 50% protein ; and iii ) determination of optimum stocking density of M . nemurus cultured intensively at six variable densities, such as 105 , 195 , 285, 375 , 465 and 555 fish/m3 respectively.